Tren Pola Konsumsi Pembaca Media Cetak di Kalangan Mahasiswa di Kota Medan - Ginting, Rahmanita (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2015)
AbstractWe cannot imagine if there were no medla in the global information era. Sut when the media and infornn.ation expose the society that is not ready to accept it, the implication raises many new problems, is the print rnech will survive in the next 10-2Ci years into the future?